The power of AAA-ATPases on the road of pre-60S ribosome maturation: Molecular machines that strip pre-ribosomal particles - Kressler, Dieter; Hurt, Ed; Baßler, Jochen (Biochimica et biophysica acta. Molecular cell research, 2012)
The biogenesis of ribosomes is a fundamental cellular process, which provides the molecular machines that synthesize all cellular proteins. The assembly of eukaryotic ribosomes is a highly complex multi-step process that requires more than 200 ribosome biogenesis factors, which mediate a broad spectrum of maturation reactions. The participation of many energy-consuming enzymes (e.g. AAA-type ATPases, RNA helicases, and GTPases) in this process indicates that the expenditure of energy is required to drive ribosome assembly. While the precise function of many of these enzymes remains elusive, recent progress has revealed that the three AAA-type ATPases involved in 60S subunit biogenesis are specifically dedicated to the release and recycling of distinct biogenesis factors. In this review, we will highlight how the molecular power of yeast Drg1, Rix7, and Rea1 is harnessed to promote the release of their substrate proteins from evolving pre-60S particles and, where appropriate, discuss possible catalytic mechanisms. This article is part of a Special Issue entitled: AAA ATPases: structure and function.